2009
DOI: 10.1038/nrneph.2009.210
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of peritoneal dialysis: a story of believers and nonbelievers

Abstract: In 2008, an estimated 1.77 million patients worldwide received dialysis. Of these patients, 1.58 million were treated with hemodialysis and approximately 190,000 received peritoneal dialyisis. In a global comparison of treatment methods for renal failure, therefore, hemodialysis clearly dominates. In this Review, we compare the epidemiology of peritoneal dialysis with that of hemodialysis and describe some of the major differences in the global utilization of the two dialysis modalities. These differences can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 50 publications
1
77
0
3
Order By: Relevance
“…Our data suggest that it may make sense to recommend that patients receive more information and education about choice of modality before dialysis initiation. As was shown previously, when patients get educated about dialysis modalities, the number of patients who decide to initiate PD increases, and the level of satisfaction also increases with the choice of modality (24,25).…”
Section: Discussionsupporting
confidence: 55%
“…Our data suggest that it may make sense to recommend that patients receive more information and education about choice of modality before dialysis initiation. As was shown previously, when patients get educated about dialysis modalities, the number of patients who decide to initiate PD increases, and the level of satisfaction also increases with the choice of modality (24,25).…”
Section: Discussionsupporting
confidence: 55%
“…This decline in PD use has been noted by others and may be explained by a few factors. 3,[15][16][17]23,24 Several economic influences, including health care financing and delivery, physician reimbursement, and resource availability, have been suggested to affect trends in use. 3 For example, countries with private dialysis providers generally use PD for a smaller proportion of dialysis patients than countries in which public providers dominate.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies that showed declining PD use in the developed world are limited by the number of countries considered and the length of time examined. 3,[15][16][17] No study has examined the global use of different PD modalities over a significant period of time, including continuous ambulatory PD (CAPD) and automated PD (APD). For these reasons, we assessed PD use worldwide by compiling data from multiple sources over a 12-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PD has been previously associated with reimbursement patterns (26). Some countries and states provide incentives for increasing the proportion of patients who use PD within publicly funded systems (25,27).…”
Section: Discussionmentioning
confidence: 99%